Development of a Japanese version of the patient perceptions of deprescribing – Short form - Mio Kushibuchi; Kenya Ie; Masaki Takahashi; Amy M. Linsky; Steven M. Albert (Journal of General and Family Medicine)
Abstract Background Deprescribing is a critical component of clinical practice, especially in geriatric medicine. Nevertheless, the attributes of patients who are prepared for, interested in, and could potentially benefit from deprescribing have not been well examined. The Patient Perceptions of Deprescribing (PPoD) evaluates patients' overall readiness for deprescribing and is complemented by an 11‐item validated short form (SF‐PPoD). The objective of this study was to develop a Japanese version of the SF‐PPoD and assess its reliability and validity within Japanese older adults with polypharmacy. Methods The SF‐PPoD was translated, back‐translated, and assessed in a cognitive interview. We conducted a cross‐sectional survey with 196 patients aged 65 years or older with five or more medications using the Japanese version to test for reliability and validity. We examined internal consistency and construct validity to determine if the Japanese sample responses reproduce the two subscales in the original SF‐PPoD. Finally, we examined intra‐person replicability using the intraclass correlation coefficient, in which 100 participants were invited and 93 participated. Results 118 males and 78 females, with a mean age of 79.2 [SD 6.5] years, completed the survey. Confirmatory factor analysis of the Japanese version of SF‐PPoD revealed satisfactory structural validity with two‐dimensional structure, “Motivation for Deprescribing” and “Primary Care Physician Relationship.” Cronbach's alpha showed good internal consistency, and test–retest demonstrated acceptable intra‐rater reliability. Conclusions We developed and validated a Japanese version of SF‐PPoD with an 11‐item, two‐dimensional structure consistent with the original SF‐PPoD. This scale may facilitate shared decision‐making for medication optimization among older adults living with multimorbidity.